Arabic Virtues in the Poetry of the Uncultivated Period that represent peace for the life of the Society (Journal of the College of Basic Education, 2023)
Every society has its own moral virtues representing its meritsThe Poetry of the Uncultivated period reflects the Arabic . and hopesmerits like honour, chastity, faith respect that were the principles ofthe Arabs to live in peace.